Assessment of Inappropriate Antibiotic Prescribing in Pediatric Febrile Illnesses - Rafia Naseem, Waseem Abbas, Nida Imdad, Tayyaba Mushtaq, Mahwish Ashraf, Ahsan Idrees, Asma Afzal, Abdul Rehman Usama (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Fever is a common cause of pediatric consultations, but most febrile illnesses in children are viral and self-limiting. Objective: To assess the frequency, pattern, and determinants of inappropriate antibiotic prescribing in pediatric patients presenting with febrile illnesses. Methodology: This cross-sectional observational study was conducted at Mayo Hospital, Lahore from December 2022 to May 2023. It included 205 children aged 1 month to 12 years presenting with fever. Data on demographics, diagnosis, antibiotic type, route, duration, and rationale were collected using a structured proforma. Appropriateness of prescriptions was evaluated according to WHO and national pediatric treatment guidelines. Results: The mean age of patients was 5.2 ± 3.1 years, with 57.1% males. Most patients (74.1%) were managed in the outpatient department. Upper respiratory tract infection (42%) was the most frequent diagnosis leading to antibiotic prescription. Cephalosporins (37.1%), penicillins (33.2%), and macrolides (16.1%) were the most prescribed classes. Inappropriate antibiotic use was found in 59% of prescriptions, significantly higher in outpatients (p = 0.042) and viral infections (p < 0.001). Children who received inappropriate antibiotics had slower fever resolution (65.3% vs 88.1%), higher readmission rates (11.6% vs 3.6%), and more adverse effects (19% vs 8.3%). Conclusion: Inappropriate antibiotic prescribing is highly prevalent in pediatric febrile illnesses, especially in viral infections and outpatient encounters. Overuse of broad-spectrum antibiotics such as cephalosporins and macrolides leads to adverse outcomes and increased resistance. Keywords: Fever, Febrile, Antibiotic, Treatment, Outcomes, Patients